2011
DOI: 10.1007/dcr.0b013e3182092e51
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Clinical Results of Double-pursestring Stapled Hemorrhoidopexy in a Selected Group of Patients for the Treatment of Chronic Hemorrhoids

Abstract: The new PPH33-03 stapler, the learning process of the modified surgical procedure, and the correct selection of patients will overcome the main objections to stapled hemorrhoidopexy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…In the literature, recurrence or persistence of hemorrhoidal prolapse after SH is reported in up to 50 % of patients, and it is generally related to the presenting symptoms and clinical stage of the disease [7,18,19]. In our series, 35 % of the patients complained of per-anal tissue prolapse after SH.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In the literature, recurrence or persistence of hemorrhoidal prolapse after SH is reported in up to 50 % of patients, and it is generally related to the presenting symptoms and clinical stage of the disease [7,18,19]. In our series, 35 % of the patients complained of per-anal tissue prolapse after SH.…”
Section: Discussionmentioning
confidence: 72%
“…Patients could report other anal/perianal lesions including skin tags or postoperative scars as tissue prolapse or recurrence. In another series with long-term follow-up, recurrence and symptomatic prolapse following SH were 7 and 3 %, respectively [18]. The majority of the previous reports favor conventional hemorrhoidectomy as regards recurrence after surgery [7].…”
Section: Discussionmentioning
confidence: 92%
“…Devices were employed per the manufacturer's instructions and local practice techniques, similar to prior publications. [11][12][13][14] Use of preoperative enemas and antibiotics, patient position (prone jackknife or lithotomy), and method of bleeding control, as needed, was per investigator discretion. Bleeding rates, interventions, and duration of treatment to control bleeding were recorded.…”
Section: Operative Techniquementioning
confidence: 99%
“…An inadequate quantity of mucosa resected during SH due to the limited capacity of the case of the PPH‐01/03 staplers (Ethicon EndoSurgery, Cincinnati, Ohio, USA) has been suggested to explain the greater recurrence. To overcome this drawback, several technical changes have been proposed including a double purse‐string suture of the rectal mucosa using the stapled trans‐anal rectal resection (STARR) technique and, more recently, using new stapling devices specifically designed to excise a larger quantity of mucosa . In a recent randomized controlled trial , we demonstrated that the new stapler EEA (Covidien, Mansfield, Massachusetts, USA) removes a larger volume (20.40 ml) of tissue with better haemostasis than the PPH‐01 stapler (Ethicon EndoSurgery; 17.3 ml).…”
Section: Introductionmentioning
confidence: 99%